P2X3 receptor involvement in endometriosis pain via ERK signaling pathway. - Shaojie Ding; Libo Zhu; Yonghong Tian; Tianhong Zhu; Xiufeng Huang; Xinmei Zhang (PLoS ONE)
The purinergic receptor P2X ligand-gated ion channel 3 (P2X3) is crucially involved in peripheral nociceptive processes of somatic and visceral pain. Endometriosis pain is considered as a kind of inflammatory and neuropathic pain. However, whether P2X3 is involved in endometriosis pain has not been reported up to date. Here, we aimed to determine whether P2X3 expression in endometriotic lesions is involved in endometriosis pain, which is regulated by inflammatory mediators through extracellular regulated protein kinases (ERK) signalling pathway. We found that P2X3 expressions in endometriosis endometrium and endometriotic lesions were both significantly higher as compared with control endometrium (P<0.05), and both positively correlated with pain (P<0.05). The expression levels of phosphorylated -ERK (p-ERK), phosphorylated-cAMP-response element binding protein (p-CREB), and P2X3 in endometriotic stromal cells (ESCs) were all significantly increased in comparison to the initial levels after treated with interleukin (IL)-1β (P<0.05) or adenosine triphosphate (ATP) (P<0.05), respectively, and did not increase after the ESCs were pre-treated with ERK1/2 inhibitor. Additionally, P2X3 and calcitonin gene related peptide (CGRP) were co-expressed in endometriotic lesions. These obtained results suggest that P2X3 might be involved in endometriosis pain signal transduction via ERK signal pathway.